Consumption and initial mortgage conditions: evidence from survey data - Giacomo Masier; Ernesto Villanueva (European Central Bank (ECB), 2011)
Economic theory predicts that the consumption path of unconstrained homeowners responds to the interest rate, while the consumption path of credit constrained homeowners is determined by the size and timing of payments (mortgage maturity). We exploit the rapid expansion of mortgage markets during the last decade in Spain and a very detailed survey on household finances to estimate group-specific consumption responses to changes in the credit conditions. Our estimates suggest that the consumption of households headed by an individual with high school respondsmore to mortgage maturity than to the interest rate spread. The consumption of the rest of indebted households is insensitive to loan maturity. Those results are confirmed when we instrument loan maturity exploiting the fact that banks are reluctant to offer contracts with age at maturity above 65. An interpretation of those results is that households headed by middle education individuals, 8% of our sample, behave as credit constrained.
Keywords: D91; E91; 330; credit constraints; household consumption; mortgages; Wohneigentum; Hypothek; Liquiditätsbeschränkung